“National Champions” and Technological “Little Giants”: Chinese Industrial Policy Between Modernization and Tradition - I. V. Danilin (Vestnik MGIMO-Universiteta)
China is confronting escalating geopolitical and socio-economic challenges, prompting a structural reorganization of its economy centered on the high-tech sector and emerging technologies. This article examines China's contemporary industrial, technological, and innovation policies within the context of global economic disruptions and domestic structural constraints. The relevance of this study lies in evaluating China's capacity to adapt to a shifting international environment, heightened technological competition from Western countries, and domestic pressures such as an aging population and slowing economic growth.The paper seeks to assess current strategies for the development of China's national innovation system (NIS) and critically analyze the transformation of its industrial policy. The central hypothesis posits that, despite outward signs of modernization, China's approach retains elements of traditional interventionism. Methodologically, the research draws on the theory of national innovation systems and elements of political economy, supplemented by case studies. These include an analysis of support mechanisms for small and medium-sized enterprises (SMEs)—particularly the so-called "small giants"—as a key example of the implementation of the "national champions" policy. The study relies on official documents and relevant statistical data.The findings reveal that China's current industrial and technological policies are marked by ambivalence. On the one hand, there is a notable shift towards a more nuanced and multitiered support system, emphasizing incentives for technology-oriented SMEs and the development of advanced sectors such as integrated circuits, artificial intelligence, and renewable energy. On the other hand, elements of a techno-centric and mobilization-oriented approach persist, with "national champions" continuing to play a central role in driving economic development. While the definition of champions has expanded to include SMEs, and the criteria for their selection have become more flexible, the effectiveness of this policy remains limited. The case of the "small giants" highlights the risks associated with the new policy framework. Looking ahead, the Chinese economy and its technology policies will continue to face significant challenges. However, the potential for transformative change appears limited due to mounting external pressures and path dependency, which predispose Chinese leadership to replicate established approaches.